The King James Bible : Christianity's definitive text - Corzine, Phyllis, 1943- (San Diego, CA : Lucent Books, 2000)
Traces the history of the King James Bible discussing how it came to be translated, the scholars involved, the sources used, and the seven years of work that produced, in 1611, a new version of the Bible that has been praised as "the noblest monument of English prose."
Includes bibliographical references (p. 87-89) and index.
Keywords: Bible. -- Versions -- Authorized -- History -- Juvenile literature; Bible. -- Versions -- Authorized -- History